Предмет: Математика,
автор: donarik1986
(76-(27+9)+8)÷6×4=
9×(2×3)-48÷8×3+7×6-34=
(7×4+33)-3×6÷2=
(9×4-6×5)×4-42÷7+(60-11)=
7×6+9×4-(2×7+54÷6×5)=
(37+7×4-17)÷6+7×5=
33+9×3-(85-67)÷2×6=
Напишите пожалуйста по действиям прошу
Ответы
Автор ответа:
0
Ответ:
1)864
Пошаговое объяснение:
Автор ответа:
1
Ответ:
1. 32
2. 44
3. 52
4. 67
5. 19
6. 43
7. 6
Пошаговое объяснение:
Похожие вопросы
Предмет: Оʻzbek tili,
автор: S35zendi
Предмет: География,
автор: Arianchik83
Предмет: Алгебра,
автор: DanyaSAMP
Предмет: Информатика,
автор: TheArtik
Предмет: Литература,
автор: Ляля77777